-3p+8=6-(8p+5)

Simple and best practice solution for -3p+8=6-(8p+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3p+8=6-(8p+5) equation:


Simplifying
-3p + 8 = 6 + -1(8p + 5)

Reorder the terms:
8 + -3p = 6 + -1(8p + 5)

Reorder the terms:
8 + -3p = 6 + -1(5 + 8p)
8 + -3p = 6 + (5 * -1 + 8p * -1)
8 + -3p = 6 + (-5 + -8p)

Combine like terms: 6 + -5 = 1
8 + -3p = 1 + -8p

Solving
8 + -3p = 1 + -8p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '8p' to each side of the equation.
8 + -3p + 8p = 1 + -8p + 8p

Combine like terms: -3p + 8p = 5p
8 + 5p = 1 + -8p + 8p

Combine like terms: -8p + 8p = 0
8 + 5p = 1 + 0
8 + 5p = 1

Add '-8' to each side of the equation.
8 + -8 + 5p = 1 + -8

Combine like terms: 8 + -8 = 0
0 + 5p = 1 + -8
5p = 1 + -8

Combine like terms: 1 + -8 = -7
5p = -7

Divide each side by '5'.
p = -1.4

Simplifying
p = -1.4

See similar equations:

| 16(2x-4)=4(8x+9) | | 6x+3+x=2+5x+5 | | 0.20t^2-45.0t+1000=0 | | 0.20t^2-45.0t=1000 | | 9+10s-4=9s+47-6s | | -16t^2+3t+1.3=0 | | -7(x+1)-13=26+3 | | -32+28=4 | | y/15+6=y/6+12 | | -9=-6+3x | | 16x^4=y^2 | | 0=2(3x-5)+8(4x+7) | | -16t^2+3t+1.3=h(t) | | 12+m/4=3d-1/2 | | (2x-3)(x+3)=3 | | 4(a+3)=6(a-(5-a)) | | 6(3+v)+36v=13v | | 7r-8r=6 | | 5xy-3y-4=0 | | X-3/5+3/5=-x/2 | | -5t-26=18t | | -(100/-4) | | 3x+9=15forx | | 0=16t^2+44t-24 | | -3/4+7/3 | | 4=2a+37 | | 4x^2=12x-8 | | -4x^2-40x-106=0 | | -17=1+4n-7n | | g(x)=2f(x) | | -4/3-1 | | 6y+4=3(2y-10) |

Equations solver categories